Revolutionary saint: the theological legacy of Óscar Romero - Lee, Michael Edward (Orbis Books, 2018)
Remembering Romero -- Romero in context: a theological coming of age -- Oscar Romero and conversion: new eyes and a new home -- Romero's faith and politics: making a preferential option for the poor -- Romero and martyrdom: witness to solidarity -- Oscar Romero, liberation theology, and a revolutionary saint